Peran Multidimensi Pelatih Dalam Mengoptimalkan Program Latihan Tim Sepak Bola: Studi Kasus Pada Lagarmanu Fc Di Desa Lemanu, Solor Selatan - Aran, Kristoforus Ado; Ruron, Antonius Harun; Melur, Yohanes Buron (Universitas Hamzanwadi, 2025)
This study aims to analyze the multidimensional role of coaches in optimizing soccer team training programs, with a case study of Lagarmanu FC in Lemanu Village. The method used is qualitative with an intrinsic case study design, where data is collected through participant observation, in-depth interviews with coaches, players, and managers, as well as document studies. The results of the study reveal that coaches play a role in four key dimensions: technical-tactical, physical, mental-motivational, and managerial. The success of the training program is determined by the coach's ability to synergistically integrate these four dimensions, with situational leadership and effective interpersonal communication. The discussion shows that this holistic approach offers novelty by consolidating the role of the coach as a tactical architect, psychologist, manager, and data analyst in a unified framework, which is in line with current leadership and sports psychology theories. The research conclusion emphasizes that optimizing training programs in the modern era requires coaches to act as “specialist generalists,” capable of synergizing sports science, psychology, management, and technology to create a holistic, player-centered training environment.